Understanding the Neuromechanisms of Consumer Behavior in Advertising Industry - Fauzan, Norsiah (European Journal of Economics and Business Studies, 2015)
The objective is to acknowledge the relevance of the unconsciousness in the consumers’ behavior by providing a new point of view based on the innovative findings of cognitive neuroscience. This paper highlights recent studies on emotion, and memory, focusing on their implication in the advertising process. The intention of this paper is to open our eyes to new scientific findings that may well mean a new way of understanding how advertising works, giving a new value to the role of emotion and consciousness. The 21st century gives us the opportunity to look once more at the perspective of incorporating validated scientific contributions based on the new discoveries about brain functioning. This article will build bridges between these scientific results and current advertising practice in a way that allows us to introduce a new point of view which redefines the influence of emotions and its role in the processes of memory, attention, reasoning and decision-making.